2010
DOI: 10.1103/physrevlett.104.095501
|View full text |Cite
|
Sign up to set email alerts
|

Nondestructive Imaging of Individual Biomolecules

Abstract: Radiation damage is considered to be the major problem that still prevents imaging an individual biological molecule for structural analysis. So far, all known mapping techniques using sufficient short wavelength radiation, be it x rays or high energy electrons, circumvent this problem by averaging over many molecules. Averaging, however, leaves conformational details uncovered. Even the anticipated use of ultrashort but extremely bright x-ray bursts of a free electron laser shall afford averaging over 10{6} m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 8 publications
1
41
0
1
Order By: Relevance
“…4,5 We have recently demonstrated that electrons with kinetic energies in the range of 50-200 eV do not cause radiation damage to biomolecules, enabling the investigation of an individual molecule for an extended period of time. 6 Since the electron wavelength associated with this kinetic energy range is between 0.86 Å (for 200 eV) and 1.7 Å (for 50 eV), low-energy electrons have the potential for nondestructive imaging of single biomolecules 7,8 and in particular individual proteins at atomic resolution.…”
mentioning
confidence: 99%
“…4,5 We have recently demonstrated that electrons with kinetic energies in the range of 50-200 eV do not cause radiation damage to biomolecules, enabling the investigation of an individual molecule for an extended period of time. 6 Since the electron wavelength associated with this kinetic energy range is between 0.86 Å (for 200 eV) and 1.7 Å (for 50 eV), low-energy electrons have the potential for nondestructive imaging of single biomolecules 7,8 and in particular individual proteins at atomic resolution.…”
mentioning
confidence: 99%
“…However, it requires Angstrom wavelengths radiation that does not destroy a single molecule before sufficient elastic scattering events have been recorded. It turns out that low-energy electrons fulfill these requirements as has recently been shown [1]. Another prerequisite for such a single molecule experiment is the ability to detect or recover the phase information to attain a one to one relation between diffraction pattern and structure of the molecule.…”
Section: Introductionmentioning
confidence: 93%
“…Experimental results suggest that DNA is a hardy substance that withstands electron radiation with electron energies in the range from 60 to 230 eV, despite a vast dose of 10 8 electrons/nm 2 accumulated over more than one hour [20]. A high electron dose is critical for achieving high throughput, as throughput scales directly with electron dose.…”
Section: Dna Sequencing By Imagingmentioning
confidence: 99%